Aula de trabalho pedagógico coletivo: uma reflexão sobre a importância das demandas do contexto e da criticidade em sua potencialidade formativa - Correa, Adriano Borba (2016)
This research aims at understanding the professional education process configuration in a school through the interactions in the professional education space called “Pedagogical Group Work Class”. Therefore, it has as specific objectives to analyze the type of professional education presented in the official documents and the work conducted by two “Pedagogical Group Work Classes” in a public State School. The research was done using the Socio-Historical-Cultural Activity Theory developed by Vygotsky (1934/2001) and Engeström (1999) and the educators critical professional education perspective. The concept of the Activity proposed in this research is that the human activity is not seen as isolated activity systems, but as a cultural relations web that through its dialogue and collaboration has a changing function. The theoretical discussion has the intention to treat the constitutive process of professional education centered in the school, according to the critical professional education proposed by Almeida and Placco (2013), Liberali (2012), and Imbernón (2009). The study has the following procedures to organize data analysis: the “Pedagogical Group Work Classes” activity analysis in the official documents and in the recorded meetings, considering the contents of the documents and of the “Pedagogical Group Work Classes” meetings, as well as the organization proposal and the way the pedagogical meetings are conducted. The results show that the official documents offer a professional education proposal that gets close to a critical perspective. But the practice that takes place in the schools has a prescriptive and technical approach due to the demands for learning results that are imposed to the schools by those who prescribe a critical professional education. This research offers a contribution to stimulate the reflection about the “Pedagogical Group Work Class” in order to break the reproductive process system and provide the construction of proposals which main objective is to make the space more critical, reflexive and collaborative, focusing on the profession education based on the contexts and demands of the school and its collabo